Kiowa Calendars and the Search for Sacred Power. (3rd July 2017) - Graber, Jennifer
Abstract: This article explores Kiowa sai - gut, or calendars produced in the 1880s and 1890s to show how makers used material culture to represent new ritual practices as both broadly indigenous and particularly Kiowa. Using calendars as one form of Kiowa cultural expression, the article considers how Kiowas navigated their reservation's changing religious landscape. Building on literature in American Indian studies that emphasizes native agency and activity in this period, the article suggests that scholars of American religions can look to forms of material culture as ways to track American Indian religious life in this period.